2009
DOI: 10.1590/s0066-782x2009001200020
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico-demográfico e indicadores de qualidade da insuficiência cardíaca em uma área rural

Abstract: Background: data on heart failure (HF) in Brazil are ensued from tertiary centers. This information can not be extended to the rural population, for it reflects distinct social, economic and cultural characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…Four studies involved both inpatient and outpatient data [22],[24],[26],[36], six studies referred solely to patients seen at outpatient clinics [27],[39],[61],[66],[67],[70], three studies described heart failure in primary care settings [62]–[64], and the remainder reported solely on inpatient populations. One study was a population-based assessment of the prevalence of heart failure in Turkey [63].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies involved both inpatient and outpatient data [22],[24],[26],[36], six studies referred solely to patients seen at outpatient clinics [27],[39],[61],[66],[67],[70], three studies described heart failure in primary care settings [62]–[64], and the remainder reported solely on inpatient populations. One study was a population-based assessment of the prevalence of heart failure in Turkey [63].…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis of heart failure was established according to the Framingham criteria [71] in 12 studies [21],[22],[24],[28][31],[42],[48],[55],[62],[70]. European Society of Cardiology guidelines were used in eight studies [25][27],[41],[50],[54],[60],[61], the Boston criteria [72] in three studies [39],[40],[47], and the American Heart Association guidelines in two studies [49],[53], and the diagnosis was left to the investigator's or examining physician's discretion in 26 studies ([19],[20],[23],[32]–[38],[43]–[46],[51],[52],[56]–[58],[64],[65],[67]–[69]; S. Rahimzadeh, F. Farzadfar F, and M. Ghaziani, unpublished data). One study diagnosed all cases of heart failure solely using echocardiography [59].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies in Brazil and around the world describe the adherence rates among hypertensive patients, especially in rural areas. Most investigations have been focused on the evaluation in urban centers and these data cannot be extended to rural areas, as populations have very different demographic characteristics, food and cultural habits, occupation types and access to health care ( 3 ) .…”
Section: Introductionmentioning
confidence: 99%